Tingupa tlingitorum, n. sp., a new milliped from Haines, Alaska, USA, with notes on the generic distribution and a revised key to species (Chordeumatida: Tingupidae) - Shear, William A.; Shelley, Rowland M. (Zootaxa, 2007)
Tingupa tlingitorum n. sp. (Diplopoda: Chordeumatida: Tingupidae) is proposed for male and female millipeds from Haines, Alaska, USA. It constitutes the first Alaskan record of the family and third of the order, and represents generic and familial range extensions of ca. 1,050 mi (1,680 km) from the previous northern limit in Oregon. Tingupa sp. is also reported from Idaho, the first generic and familial records from this state, and the Queen Charlotte Islands, the first records for both Canada and British Columbia. A revised key to species and a new familial distribution map are presented.